Motherhood in the Context of Intimate Partner Violence: Towards a Matricentric Perspective - Malažinskienė, Jolanta (Socialinė teorija, empirija, politika ir praktika, 2025)
Intimate partner violence against women continues to be a major problem worldwide. The problem is exacerbated when women are subjected to violence as mothers, whose experiences are marginalised because of attention dedicated to their children. This article explores how the concepts of mothers and motherhood are constructed in the child welfare literature, which traditionally views mothers as solely responsible for children’s well-being, even in the case of violence against them. The first part of the paper discusses the features of child welfare research in the context of intimate partner violence against mothers, whereas the second part of the paper discusses the aspects that underpin the construction of images of mothers and motherhood in this literature, while the third part of the paper highlights the importance of the matricentic perspective in research on mothers’ experiences of violence.